Corporate social responsibility (CSR) disclosure by Malaysian listed property companies / Asma Senawi ... [et al.] - Senawi, Asma; Saleh, Nor Aini; Abdul Rahman, Nor Azalina Yusnita; Che Pin, Siti Fairuz (2012)
The concept of corporate social responsibility (CSR) is receiving spectacular attention in recent years both from the business practitioners as well as academicians in different parts of the world. Corporate social responsibility (CSR) is a company's commitment to operating in an economically, socially and environmentally sustainable manner whilst balancing the interests of diverse stakeholder. As stated in Status Report by Bursa Malaysia in 2007, there are four dimension of CSR i.e. environment, community, marketplace and workplace. This exploratory research designed to investigate the level of corporate social responsibility (CSR) disclosure among Malaysian Property Listed Companies. To measure the extent of disclosure made by companies, CSR Disclosure Index was developed specifically for property companies. Content analysis had been used to analyse the activities carried out by companies using annual report and company's websites. 20 property companies listed in the Main Board of Bursa Malaysia was selected randomly. This study reports that a very few property companies in Malaysia are making efforts to carry out CSR practice in their business since the enforcement by Bursa Malaysia in 2006. The highest CSR disclosure's dimension is community involvement followed by environment, marketplace and workplace. To better performance in the future, Malaysian companies is suggested to improve their level of CSR disclosure as isn't only benefits the company itself but also to the society. Government intervention is needed to increase the level of CSR practice in Malaysia.